Heat conduction in a truncated wedge of semi-infinite height wiht circular boundaries - Kalla, S. L.; Jain, S.; Goyal, S. P.; Vasistha, S. K. (Rev. Téc. Fac. Ing. Univ. Zulia)
In this paper, the problem of finding the temperature at any point of a truncated wedge of semi-infinite height, with circular boundaries, when there are sources of heat within it, for boundary conditions of the radiation type is considered. Different types of integral transforms are employed to solve the problem.